TECHNO-ECONOMIC FEASIBILITY AND EMISSION REDUCTION OF 60 MW WIND POWER PLANTS FOR DATA CENTER IN WEST JAVA INDONESIA USING RETSCREEN - Indra Fatah; Dzikri Firmansyah Hakam; Diwangkara Bagas Nugraha (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
The rise of Indonesia’s digital economy has accelerated the need for green data centers powered by clean energy. Aims: This research aims to evaluate the techno-economic feasibility and environmental impact of integrating a 60 MW wind power plant to supply electricity for potential green data center locations in West Java. Methodology and results: Using RETScreen Expert software, the analysis incorporates turbine specifications, site-specific climate data from ERA5 and NASA, and financial assumptions sourced from independent power producer developers in Indonesia. Output analysis focuses on environmental metrics such as GHG emissions and financial indicators including NPV, IRR, and payback periods. The analysis shows that the project can produce close to 120 GWh electricity annually that will provide about USD 8.5 million/year based on 20 years of operation and reduce 222,931 tCO₂ of GHGs annually, or a 24.7% reduction compared to that of a 128 MW coal-fired power plant. Financially, the project achieves an NPV of USD 4.1 million, an after-tax IRR of 12.2%, and a payback period of 10.3 years. Conclusion, significance and impact study: These findings confirm the strategic importance of wind power plants in supporting sustainable digital infrastructure in Indonesia. This research helps bridge the existing literature gap in renewable energy integration for data centers in emerging markets. Additionally, it suggests that future studies could explore hybrid renewable models to enhance system resilience and reliability.